1999
DOI: 10.1046/j.1523-1755.1999.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Lp(a) and LDL induce apoptosis in human endothelial cells and in rabbit aorta: Role of oxidative stress

Abstract: Atherogenic lipoproteins stimulate O2- formation and induction of apoptosis in HUVECs and RA, and may thereby influence the pathogenesis of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
63
1
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 52 publications
11
63
1
4
Order By: Relevance
“…For example, aortic SMCs obtained from hSod1Tg ϩ/0 and hCatTg ϩ/0 mice, compared with aortic SMCs from their wild-type littermates, showed a 50% decrease in the percentage of cells with DNA fragmentation and a 50% decrease in caspase activity induced by oxLDL. These results are consistent with the observations of Galle et al 9 showing that the addition of SOD or catalase to the culture medium blunted apoptosis induced by oxLDL. In addition, we observed that aortic SMCs obtained from Sod2 ϩ/Ϫ and Gpx1 Ϫ/Ϫ mice showed a significant increase in the percentage of cells with DNA fragmentation and a significant increase in caspase activity compared with wild-type mice.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…For example, aortic SMCs obtained from hSod1Tg ϩ/0 and hCatTg ϩ/0 mice, compared with aortic SMCs from their wild-type littermates, showed a 50% decrease in the percentage of cells with DNA fragmentation and a 50% decrease in caspase activity induced by oxLDL. These results are consistent with the observations of Galle et al 9 showing that the addition of SOD or catalase to the culture medium blunted apoptosis induced by oxLDL. In addition, we observed that aortic SMCs obtained from Sod2 ϩ/Ϫ and Gpx1 Ϫ/Ϫ mice showed a significant increase in the percentage of cells with DNA fragmentation and a significant increase in caspase activity compared with wild-type mice.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we observed that aortic SMCs obtained from Sod2 ϩ/Ϫ and Gpx1 Ϫ/Ϫ mice showed a significant increase in the percentage of cells with DNA fragmentation and a significant increase in caspase activity compared with wild-type mice. Results from Galle et al 9 and from our studies indicate that antioxidant enzymes protect vascular cells from apoptosis induced by oxLDL. Antioxidant enzymes also have been found to protect cells against apoptosis induced by other types of stimuli.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…2). Las lipoproteínas aterogénicas, especialmente las formas oxidadas, podrían ser las inductoras de la apoptosis de las células endoteliales en el contexto de la aterosclerosis [35][36][37] .…”
Section: Apoptosis De Las Células Endotelialesunclassified